2016
DOI: 10.1590/0103-8478cr20150472
|View full text |Cite
|
Sign up to set email alerts
|

Grape yield, and must compounds of 'Cabernet Sauvignon' grapevine in sandy soil with potassium contents increasing

Abstract: Content of exchangeable potassium (K) in t soil may influence on its content in grapevines leaves, grape yield, as well as, in must composition. The study aimed to assess the interference of exchangeable K content in the soil on its leaf content, production and must composition of 'Cabernet Sauvignon' cultivar. In September 2011, in Santana do Livramento (RS) five vineyards with increasing levels of exchangeable K in the soil were selected. In the 2012/13 and 2013/14 harvests, the grape yield, yield components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
0
15
2
Order By: Relevance
“…However, viticulture involves fertilizer application: in Brazil, for instance, nearly 44% of the expenses are utilized for soil amendments such as acidity correctives accounting around 13% for the total cost of vineyard maintenance and production (>4 years) (IEG/FNP, 2017). Therefore, the fertilizer application must be monitored and used only when needed, and in judicious doses, to raise the soil nutrient availability necessary to maintain the requisite nutritional status (Ciotta et al, 2016) and to ensure a high quality and compensatory harvest (Piccin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, viticulture involves fertilizer application: in Brazil, for instance, nearly 44% of the expenses are utilized for soil amendments such as acidity correctives accounting around 13% for the total cost of vineyard maintenance and production (>4 years) (IEG/FNP, 2017). Therefore, the fertilizer application must be monitored and used only when needed, and in judicious doses, to raise the soil nutrient availability necessary to maintain the requisite nutritional status (Ciotta et al, 2016) and to ensure a high quality and compensatory harvest (Piccin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these forms of K (native to the soil), mainly those available in the solution, can be cyclized by native or implanted vegetation (Pérez-Álvarez et al, 2015;Oliveira et al, 2016) such as cover crop species found in vineyards -this process reduces the availability of K forms in the soil over time (Oliveira et al, 2016). On the other hand, part of K available in the control soil and in treatments, in the assessed seasons, possibly derived from pre-planting fertilization, which was carried out before vineyard installation (Schmitt et al, 2014;Dalbó et al, 2015;Ciotta et al, 2016) -this procedure is natural in experiments ran in orchards or vineyards installed during crop production (Dalbó et al, 2015;Ciotta et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, estimates about soil exchangeable K are not always related to yield parameters or to grape yield in producing vineyards, since vines' root system exploits a larger soil volume than the herein sampled soil volume (Tramontini et al, 2013; CQFS-RS / SC, 2016) and has internal nutrient reserves, including K (Pradubsuk & Davenport, 2010). Therefore, estimates of nutrient concentrations, such as estimates of K content in leaves, (assessed at full bloom or at berries-color-change time) can be closely related to vineyards' yield parameters, as well as to grape must oenological parameters such as (TST), pH, total titratable acidity (ATT), malic acid, among other parameters (Ciotta et al, 2016;Messiga et al, 2016) that can influence the quality of the wine (Walker & Blackmore, 2012). It is likely estimating K critical level in leaves (collected at full bloom) to assess oenological quality parameters in grape must, since these parameters can also apply to other wine types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wine production, an important character to be analyzed is the amount of potassium in the must and wine, being this one of the main nutrients required for the grapevine, and one of the macronutrients most required by this species (Ciotta et al, 2016). Potassium is a dominant cation in wines at average concentration of 1 g L -1 (Riberau-Gayon et al, 2003).…”
Section: Introductionmentioning
confidence: 99%